Autophagy Regulation and Photodynamic Therapy: Insights to Improve Outcomes of Cancer Treatment - Martins, Waleska K.; Belotto, Renata; Silva, Maryana N.; Grasso, Daniel; Suriani, Maynne D.; Lavor, Tayná S.; Itri, Rosangela; Baptista, Mauricio S.; Tsubone, Tayana M. (Frontiers in Oncology, 2021)
Cancer is considered an age-related disease that, over the next 10 years, will become the most prevalent health problem worldwide. Although cancer therapy has remarkably improved in the last few decades, novel treatment concepts are needed to defeat this disease. Photodynamic Therapy (PDT) signalize a pathway to treat and manage several types of cancer. Over the past three decades, new light sources and photosensitizers (PS) have been developed to be applied in PDT. Nevertheless, there is a lack of knowledge to explain the main biochemical routes needed to trigger regulated cell death mechanisms, affecting, considerably, the scope of the PDT. Although autophagy modulation is being raised as an interesting strategy to be used in cancer therapy, the main aspects referring to the autophagy role over cell succumbing PDT-photoinduced damage remain elusive. Several reports emphasize cytoprotective autophagy, as an ultimate attempt of cells to cope with the photo-induced stress and to survive. Moreover, other underlying molecular mechanisms that evoke PDT-resistance of tumor cells were considered. We reviewed the paradigm about the PDT-regulated cell death mechanisms that involve autophagic impairment or boosted activation. To comprise the autophagy-targeted PDT-protocols to treat cancer, it was underlined those that alleviate or intensify PDT-resistance of tumor cells. Thereby, this review provides insights into the mechanisms by which PDT can be used to modulate autophagy and emphasizes how this field represents a promising therapeutic strategy for cancer treatment.